1978
DOI: 10.1002/aja.1001510304
|View full text |Cite
|
Sign up to set email alerts
|

An ultrastructural study of developing extracellular matrix in vitelline blood vessels of the early chick embryo

Abstract: This investigation was designed to describe the morphological events in embryonic development of peripheral blood vessels (vasculogenesis) and to relate this process to the appearance of extracellular matrix (ECM) during growth and maturation of these tissues. Extraembryonic vitelline vessels of the early chick embryo were chosen for this study and light, transmission, and scanning electron microscopy were carried out on vessels excised from chick embryos (Hamburger-Hamilton stages 8 through 23). Our data show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
24
1

Year Published

1979
1979
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 31 publications
5
24
1
Order By: Relevance
“…A similar model for the early separation of cells contributing to the BC/EC lineage and cells contributing to the extraembryonic coelomic linings was proposed by Sabin (Sabin, 1920), although the SMC nature of coelomic lining cells was not clearly mentioned in that report. The general anatomical organization, proposed in this work, of the extraembryonic mesoderm in the chick embryo, is also supported by ultrastructural studies (Kessel and Fabian, 1985;Murphy and Carlson, 1978).…”
Section: Research Articlesupporting
confidence: 55%
See 1 more Smart Citation
“…A similar model for the early separation of cells contributing to the BC/EC lineage and cells contributing to the extraembryonic coelomic linings was proposed by Sabin (Sabin, 1920), although the SMC nature of coelomic lining cells was not clearly mentioned in that report. The general anatomical organization, proposed in this work, of the extraembryonic mesoderm in the chick embryo, is also supported by ultrastructural studies (Kessel and Fabian, 1985;Murphy and Carlson, 1978).…”
Section: Research Articlesupporting
confidence: 55%
“…1A). The BC/EC progenitors aggregate to form blood islands within the extraembryonic splanchnic mesoderm, which contains in addition vascular SMCs (Kessel and Fabian, 1985;Murphy and Carlson, 1978;Sabin, 1920). The extraembryonic somatic mesoderm gives rise to mesothelial cells lining the ectoderm, from which the amnionic and chorionic membranes are derived (Adamstone, 1948;Oppenheim, 1966;Pierce, 1933;Romanoff, 1960;Wu et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The splanchnic wall of the extraembryonic coelom is the source of cells for the vascular smooth muscle layer during vasculogenesis, and after formation of the vascular network, vascular smooth muscle layer is in direct contact with the extraembryonic coelomic cavity. This general organization of somatopleural and splanchnopleural tissues in the yolk sac is supported by ultrastructure studies (Kessel and Fabian, 1985;Murphy and Carlson, 1978).…”
Section: Extraembryonic Mesoderm and Ventral Mesodermmentioning
confidence: 50%
“…For many years, differentiation and maturation of VSMCs has been correlated to changes in the ECM composition of the vessel wall. Studies from Murphy and Carlson [216]suggested that ultrastructural differentiation of presumptive VSMCs occurs concomitantly with synthesis of specific ECM proteins. Within early embryonic chicken vitelline vessels (embryonic days 1–4) two distinct cell layers, representing the early endothelium and presumptive VSM, are observed in the vessel wall by transmission electron microscopy at stage 10, no ECM material is apparent.…”
Section: Extracellular Environmentmentioning
confidence: 99%